Teaching programming for students remotely during social isolation due to the COVID-19 pandemic - Silva , Janielly Maria da; Silva , Claudete de Jesus Ferreira da; Monteiro , Francisca Ocilma Mendes (Seven Editora, 2023)
Due to the Pandemic caused by Covid-19, schools had to quickly adapt teaching to students. Faced with this situation, teachers had to overcome the challenges during this experienced period, and students had to learn to assimilate the contents remotely. Despite the difficulties and challenges faced by the professors, it was also an opportunity to learn how to use new technologies to assist in teaching and learning.   The work had as a data collection instrument an online questionnaire produced in Google Forms, a questionnaire answered in person with the students, and an interview with two programming teachers of the school, anonymous and voluntary, being sent to the José Pacifico School of Moorish. It is noteworthy that we are going through moments of transformation and adaptation, in which we continue to learn and create new forms of teaching strategies.  In this sense, technology becomes a positive strategy and contributes to student learning in remote learning, providing new ways to teach and learn. DOI:https://doi.org/10.56238/emerrelcovid19-003